Anti-clockwise: Building a critical mass against clock time. Issue 1 (1st December 2020) - Schmid, Helga; Walker, Kevin
'Uchronian Critical Mass' exploits the historical opportunity the COVID-19 pandemic and resulting quarantines have opened up to question societal time systems, which can conflict with natural rhythms, leading to adverse effects on mental and physical health. We describe an experiment in which participants step outside societal time, choose their own time-giver and live by it for up to one week. As an experiment in artistic research grounded in science, we specifically enlisted fellow artists and asked them to document their experiment using any chosen means. The results included unexpected social and spiritual qualities, evidenced increased concentration and productivity, and drew attention to aspects of societal time generally taken for granted by introducing non-linear temporal elements. The experiment impacted each artist's working practices and subsequent work. Collectively, the results show the potential of artistic practice to influence a broader questioning of societal time through multisensory means, highlighting the unique role artists hold as outsiders to lead the way in forming creative approaches to social and political issues.